Effect of Lactobacillus ramensus probiotic use and High Intensity Interval Training on the ratio of liver enzymes AST/ALT in desert mice with steatosis - Saeed Shahmohammadi; Farshad Ghazalian; Hossein Shirvani; Hossein Abednatanzi (فصلنامه ابن سینا)
Background and aims: Fatty liver is one of the increasing diseases. Since changes in the gut microbiome causes fatty liver, taking probiotics may help to maintain gut microbial balance. This study was aimed to investigate the effect of probiotics consumption along with high intensity interval training (HIIT) on the ratio of liver enzymes (AST/ALT) in rats with steatosis. Methods: In this experimental study, 40 male rats with an average weight of 200 to 250 grams were randomly divided into 5 groups of 8 (including healthy control, steatosis, HIIT+steatosis, probiotic+steatosis, HIIT+ probiotic+steatosis). They received high-fat emulsion (10 mg/kg/day) to induce steatosis. The probiotic consumption groups received 109 colonies/ml of Lactobacillus rhamnosus bacteria by gavage daily for 5 weeks and 5 days a week. The ratio of AST/ALT in the groups was compared. Results:. The ratio of AST/ALT in the steatosis group was higher than the healthy control group. However, this ratio in steatosis+exercise+probiotic group compared to the steatosis group had the highest decrease than the other intervention groups which shows the positive effect of probiotic consumption and HIIT on improving rats with steatosis (p=0.001). Conclusion: Lactobacillus rhamnosus probiotics foods consumption along with HIIT led to reduce the ratio of liver enzymes in mice with steatosis.